The Role of the Government in Empowering Persons with Social Welfare with Physical Disabilities: Peran Pemerintah Dalam Pemberdayaan Penyandang Kesejahteraan Sosial Disabilitas Tubuh - Widowati, Mahdalia Ratih; Agustina, Isna Fitria (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to analyze and describe the Government's Role in Empowering Persons with Social Welfare with Disabilities (a case study at UPT Social Rehabilitation Bina Daksa Pasuruan Regency). The type of research is descriptive qualitative research. Data collection techniques were carried out through observation, interviews and documentation. This research uses purposive sampling technique. Data analysis was carried out with data collection techniques, data reduction, data presentation, and drawing conclusions. The results of the research here show that the Government's Role in Empowering Persons with Social Welfare with Disabilities (a case study at the UPT Social Rehabilitation Bina Daksa Pasuruan Regency) is: the role as a stabilizer by socializing and providing counseling to the community and parents of people with disabilities about empowering people with disabilities. The role of the government as an innovator by providing information to the public and families of people with disabilities UPT Social Rehabilitation Bina Daksa using print media.